Etiologic Factors of Infertility in a Referral Hospital (BSMMU, Bangladesh) - Rokeya Anwar, Begum; Fatima, Parveen; Afza, Nasim; Tarannum, Tazkia; Begum, Nazneen; Umme Kulsum, Syeda; Parveen, Shaila (Journal of Medicine, 2014)
Background: Infertility is defined as the failure in pregnancy after one year of unprotected intercourse. Several centers have reported different causes of infertility. The most common causes of infertility include: Female factors such as ovulation dysfunction and tubal factor; male factors like sperm disturbance as well as ; both male and female factors and unexplained infertility. The aim of this study was to find out the etiologic factors of infertility in BSMMU (Bangabandhu Sheik Mujib Medical University, Dhaka, Bangladesh) Methods: This cross sectional study was done at the Out Patient Department (OPD) of infertility in BSMMU during the period of December 2004 to March 2005. One hundred infertile couples with necessary investigations were reviewed for the study. Results: In this study the frequency of primary and secondary infertility was 56% and 44% respectively. Among 100 couples 57% had female factor, 25% had both male and female factors and in 3% had male factor and in 15% of couple, the causes of infertility were unknown. Among women, different infertility factors included: Tubal factor 33%, Ovarian factor 12% and endometriosis 11%. In this study tubal blockage were detected in 50% cases of female secondary subfertility following Menstruation Regulation (M/R). Result showed 82% of men had normal spermogram 28%, had sperm disturbance including Oligospermia, Asthenospermia, Oligoasthenospermia and teratospermia. Conclusion: Although female factor was the most common cause of infertility in BSMMU, we can not conclude that this factor is the most common causes of infertility in Bangladesh. Since this centre is considered as referral centre especially for female infertility. We suggest performance of similar researches with big sample size in different institution to evaluate most common causes of infertility in Bangladesh. DOI: http://dx.doi.org/10.3329/jom.v14i2.18460 J Medicine 2013, 14(2): 110-113